Adjustment: Applying Psychology in a Complex World - Feldman S. R. (New York St. Louis San Francisco Auckland McGraw-Hill Book Company, 1989)
This basic text covers fundamental principles of psychology and how to apply them to everyday life. The objective is to provide an accessible text full of interesting pedagogical aids that will communicate how these principles can be used in adjusting to a variety of life situations.
Keywords: 159.9